The Use of Miniature Joglo Houses in Learning to understand Plane and Solid Figure - Muhammad Nauval Muwaffiq; Suparni Suparni Suparni (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2022)
Abstract:Learning with an ethnomathematical approach based on Realistic Mathematics Education (RME) can help students understand mathematical problems based on the culture they experience. This article examines the use of the Joglo House miniature props on planes and solid figures. This research is explorative with an ethnographic approach. The methods used are exploration, observation, documentation, and literature study. The results showed that the Joglo house can be used as an illustration in studying the elements and properties of planes and solid figures. Students can be directly involved in understanding the shapes of squares, rectangles, trapezoids, and cuboids. Students can also understand the concept of congruence well. Exploration of mathematical elements in the miniature of the Joglo House is highly recommended so that students are not fixated only on the stage of knowledge of geometric shapes.Abstrak:Pembelajaran dengan pendekatan ethnomathematical berbasis Realistic Mathematics Education (RME) dapat membantu siswa memahami masalah matematika berdasarkan budaya yang dialaminya. Artikel ini mengkaji penggunaan miniatur rumah Joglo untuk memahami konsep bangun datar dan bangun ruang. Penelitian ini bersifat eksploratif dengan pendekatan etnografi. Metode yang digunakan adalah eksplorasi, observasi, dokumentasi, dan studi pustaka. Hasil penelitian menunjukkan bahwa rumah Joglo dapat digunakan sebagai ilustrasi dalam mempelajari unsur dan sifat bangun datar dan bangun datar. Siswa dapat terlibat langsung dalam memahami bentuk persegi, persegi panjang, trapesium, dan balok. Siswa juga dapat memahami konsep kekongruenan dengan baik. Eksplorasi unsur matematika pada miniatur Rumah Joglo sangat dianjurkan agar siswa tidak terpaku hanya pada tahap pengetahuan bentuk bangun datar dan bangun ruang saja.